CONTINUOUS TRAINING OF PUBLIC SCHOOL TEACHERS - de Castro, Larrey Setimi; Ribeiro, Marilena Fernandes (Seven Editora, 2025)
This article aims to discuss the main challenges and possibilities related to the continuing education of public school teachers, highlighting public policies, training practices and the importance of teacher engagement in this process. The methodology is a bibliographical research with a descriptive and exploratory approach. The results showed that the continuing education of public school teachers is a complex challenge, but essential for the construction of quality education. Ensuring adequate conditions so that teachers can participate in relevant training, connected to their reality, is a commitment that must be assumed by managers, public policies and society in general. In this sense, it was concluded that overcoming structural difficulties and valuing the professional development of teachers are necessary paths to transform public education into a more effective and humanizing learning space. DOI: https://doi.org/10.56238/sevened2025.038-055